Anticancer activity of paclitaxel-loaded keratin nanoparticles in two-dimensional and perfused three-dimensional breast cancer models - Foglietta F (Dove Medical Press, 2018)
Federica Foglietta,1 Giulio C Spagnoli,2,3 Manuele Giuseppe Muraro,2 Marco Ballestri,4 Andrea Guerrini,4 Claudia Ferroni,4 Annalisa Aluigi,4 Giovanna Sotgiu,4 Greta Varchi4 1Department of Drug Science & Technology, University of Torino, Torino, Italy; 2Department of Biomedicine, University of Basel and University Hospital of Basel, Basel, Switzerland; 3Institute of Translational Pharmacology, CNR, Rome, Italy; 4Institute for Organic Synthesis & Photoreactivity, National Research Council, Bologna, Italy Purpose: Taxanes are highly effective cytotoxic drugs for progressing breast cancer treatment. However, their poor solubility and high toxicity urge the development of innovative formulations of potential clinical relevance. Materials and methods: By using a simple and straightforward aggregation method, we have generated paclitaxel (PTX) loaded in keratin nanoparticles (KER-NPs-PTX). Their activities were tested against human breast cancer MCF-7 and MDA MB 231 cell lines in conventional two-dimensional (2D) cultures and in a dynamic three-dimensional (3D) model with perfused bioreactor (p3D). Moreover, KER-NPs-PTX activity was compared to free PTX and to PTX loaded in albumin nanoparticles (HSA-NPs-PTX). Cell viability, induction of apoptosis, and gene expression analysis were used as readouts. Results: In 2D cultures, KER-NPs-PTX was able to inhibit tumor cell viability and to induce apoptosis similarly to PTX and HSA-NPs-PTX. In the p3D model, a lower sensitivity of tumor cells to treatments was observed. Importantly, only KER-NPs-PTX was able to induce a statistically significant increase in apoptotic cell percentages following 24 h treatment for MCF-7 (16.7±4.0 early and 11.3±4.9 late apoptotic cells) and 48 h treatment for MDA MB 231 (21.3±11.2 early and 10.5±1.8 late apoptotic cells) cells. These effects were supported, at least for MCF-7 cells, by significant increases in the expression of proapoptotic BAX gene (5.8±0.5) 24 h after treatment and of cleaved caspase 3 (CC3) protein. Conclusion: KER-NPs-PTX, generated by a simple procedure, is characterized by high water solubility and enhanced PTX-loading ability, as compared to HSA-NPs-PTX. Most importantly, it appears to be able to exert effective anticancer activities on breast cancer cells cultured in 2D or in p3D models. Keywords: keratin, nanoparticles, paclitaxel, breast cancer, perfused three-dimensional models